EKSISTENSI HUKUM ADAT DALAM MENYELESAIKAN KEKERASAAN DALAM RUMAH TANGGA DI DESA PINJAUAN KANAGARIAN PILUBANG KECAMATAN SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - Putri Asri Sri Rahayu; Erdianto Effendi; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a state of law (rechstaat) where the legal provisions rely or are guided by the Pancasila and the 1945 Constitution, as a rule they must not conflict with higher laws because they apply nationally. But in social life besides national law, there are also laws that grow and develop in society, where the law is born from the habits or attitudes and behavior of the people themselves who are often referred to as habits. This custom or habit will develop into a provision called adat law. That customary law still lives in each region. Particularly in the Penagarian Village of Pilubang Village, Sungai Limau Subdistrict, Padang Pariaman District, customary law still exists used by the community in resolving criminal acts of domestic violence. For this reason, the writer is interested in conducting research as a scientific work in the form of a thesis with the title "Existence of Customary Laws in Resolving Domestic Violence in the Kanagarian Pilubang Village, Sungai Limau District, Padang Pariaman District".The purpose of this study is to find out: first how the implementation of settlement of domestic violence in the village of Pubang Kanagarian Pilubang District Sungai Limau. second, how are the obstacles faced in resolving domestic violence in the village of Pubang Kanagarian Pilubang, Sungai Limau District. In this study the author uses empirical (sociological) juridical writing methods, namely an approach to the problem by looking at the applicable legal norms, connected with the facts in the problems encountered.From the results of the study it can be concluded that. Settlement of domestic violence in the Pilubang Kanagarian Village is a preparation, determining the day and date, as well as the location of the traditional session to be held, deliberation to decide the domestic violence case, giving advice by traditional leaders and religious leaders, paying the agreed fines. The constraints faced in resolving domestic violence in Desa Pinjauan are self factors, law enforcement factors, community factors, cultural factors.Keywords: Existence-Customary Law-Domestic Violence